2022
DOI: 10.1002/btpr.3298
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid abundance and composition in cell culture medium affects trace metal tolerance and cholesterol synthesis

Abstract: Amino acid compositions of cell culture media are empirically designed to enhance cell growth and productivity and vary both across media formulations and over the course of culture due to imbalance in supply and consumption. The interconnected nature of the amino acid transporters and metabolism suggests that changes in amino acid composition can affect cell physiology. In this study, we explore the effect of a step change in amino acid composition from a DMEM: F12-based medium to a formulation varying in rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 103 publications
2
14
0
Order By: Relevance
“…CHO cells routinely maintained in HDFE medium were inoculated into HAA media. 6 Briefly, HAA medium is formulated identically to HDFE with the exception of cysteine at 0.05 mM, cystine at 0.3 mM and all other amino acids at 1 mM concentration. Both HDFE and HAA media are formulated with 2.25 μM ZnCl 2 .…”
Section: Investigation Of the Involvement Of Groups Of Amino Acidsmentioning
confidence: 99%
See 4 more Smart Citations
“…CHO cells routinely maintained in HDFE medium were inoculated into HAA media. 6 Briefly, HAA medium is formulated identically to HDFE with the exception of cysteine at 0.05 mM, cystine at 0.3 mM and all other amino acids at 1 mM concentration. Both HDFE and HAA media are formulated with 2.25 μM ZnCl 2 .…”
Section: Investigation Of the Involvement Of Groups Of Amino Acidsmentioning
confidence: 99%
“…We chose 30 μM ZnCl 2 based on our previous work where this concentration induced toxicity in low amino acid concentrations but not in HAA or HDFE. 6 The concentration of each of the 20 amino acids was varied in at least one of the experimental conditions. The exact amino acid formulations evaluated in this study are indicated in TablesS1 and S2.…”
Section: Investigation Of the Involvement Of Groups Of Amino Acidsmentioning
confidence: 99%
See 3 more Smart Citations